Artystone bolivianensis n.sp. (Isopoda, Cymothoidae) from a loricariid catfish of the Bolivian Amazon - Thatcher, Vernon E.; Schindler, Ingo (Amazoniana, 1999)
Artystone bolivianensis n.sp. (Isopoda, Cymothoidae) from the body cavity of a Bolivian freshwater fish, Otocinclus vestitus COPE, (Loricariidae) is described. The new species most closely resembles Artystone minima THATCHER & CARVALHO, 1988, from the body cavity of Nannostomus beckfordi GÜNTHER, (Lebiasinidae) from the upper Rio Negro of Brazil. Although the two species are of similar size, the new species differs in having adult females that are about 25 % wider and more sparsely pigmented. Males of the new species are slender but have a pleon that is wider in relation to the pereon than is the case in males of the other species. The two species are from different host fish, representing two unrelated families and they are from widely separated geographic areas.